Development, Identification, and Application of a Germplasm Specific SCAR Marker for Dendrobium officinale Kimura et Migo - Zheng, Kaixin; Cai, Yuchen; Chen, Weijie; Gao, Yadi; Jin, Jingjing; Wang, Huizhong; Feng, Shangguo; Lu, Jiangjie (Frontiers in Plant Science, 2021)
The stems of Dendrobium officinale have been used as a rare and precious Chinese tonic medicine named “Tiepi Fengdou” since the Qing dynasty. Because of increased market demand and continued predatory exploitation, the reserves of wild D. officinale resources have been depleted and the adulteration of D. officinale products on the market is growing. Such changes have largely affected the sustainable utilization of this precious medicinal plant resource and the development of related industries. In this study, a species-specific DNA marker was developed for the fast and accurate authentication of D. officinale. In total, 36 start codon-targeted (SCoT) polymorphism primers were screened in 38 individuals of 36 Dendrobium species, and a clear species-specific DNA amplicon (SCoT13-215) for D. officinale was captured. After cloning and sequencing, a sequence-characterized amplified region marker was developed (named SHF/SHR) and validated through PCR amplification of all 38 Dendrobium samples. The marker’s specificity for D. officinale was confirmed by the consistent amplification of a clear 197-bp band. This SCAR marker can be used to rapidly, effectively, and reliably identify D. officinale among Dendrobium species and plays an important role in the quality control of medicinal preparations and protection of the germplasm of this important medicinal species.